Projecting the effects of climate change on the distribution of maize races and their wild relatives in Mexico - Ureta, C.; Martínez Meyer, E.; Perales R.H.; Álvarez Buylla, E.R. (Wiley, 2012)
Climate change is expected to be a significant threat to biodiversity, including crop diversity at centers of origin and diversification. As a way to avoid food scarcity in the future, it is important to have a better understanding of the possible impacts of climate change on crops. We evaluated these impacts on maize, one of the most important crops worldwide, and its wild relatives Tripsacum and Teocintes. Maize is the staple crop in Mexico and Mesoamerica, and there are currently about 59 described races in Mexico, which is considered its center of origin . In this study, we modeled the distribution of maize races and its wild relatives in Mexico for the present and for two time periods in the future (2030 and 2050), to identify the potentially most vulnerable taxa and geographic regions in the face of climate change. Bioclimatic distribution of crops has seldom been modeled, probably because social and cultural factors play an important role on crop suitability. Nonetheless, rainfall and temperature still represent a major influence on crop distribution pattern, particularly in rainfed crop systems under traditional agrotechnology. Such is the case of Mexican maize races and consequently, climate change impacts can be expected. Our findings generally show significant reductions of potential distribution areas by 2030 and 2050 in most cases. However, future projections of each race show contrasting responses to climatic scenarios. Several evaluated races show new potential distribution areas in the future, suggesting that proper management may favor diversity conservation. Modeled distributions of Tripsacum species and Teocintes indicate more severe impacts compared with maize races. Our projections lead to in situ and ex situ conservation recommended actions to guarantee the preservation of the genetic diversity of Mexican maize.